(untitled) (Web of Teachers: Inderscience Research, 2023)
The connection between the methodology of teaching a foreign language and linguistics has taken place throughout the history of the development of methodology as a science. This connection is obvious, since it is linguistics that develops the general methodological foundations of language learning, analyzes specific language material, and gives it a scientifically based objective interpretation.